Existence of projected solutions for quasi-variational hemivariational inequality - Guan Fei; Cen Jinxia; Chen Boling; Yao Jen-Chih (Demonstratio Mathematica, 2024)
In this short article, we prove the existence of projected solutions to a class of quasi-variational hemivariational inequalities with non-self-constrained mapping, which generalizes the results of Allevi et al. (Quasi-variational problems with non-self map on Banach spaces: Existence and applications, Nonlinear Anal. Real World Appl. 67 (2022), 103641, DOI: https://doi.org/10.1016/j.nonrwa.2022.103641.)